2017
DOI: 10.3390/nu9090989
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Nutritional Status of Vitamin A per Trimester of Pregnancy with Maternal Anthropometry and Anemia after Roux-en-Y Gastric Bypass

Abstract: The aim of this study was to compare the nutritional status of vitamin A per trimester of pregnancy, as well as to assess its influence on pre-pregnancy BMI, total gestational weight gain (TGWG) and presence of anemia in women who had previously undergone Roux-en-Y gastric bypass (RYGB). An analytical, longitudinal and retrospective study comprising 30 pregnant women who had previously undergone RYGB was undertaken. In all trimesters of pregnancy, the serum concentrations of retinol, β-carotene, stages of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
8
0
4
Order By: Relevance
“…In line with previous studies [13, 42], we observed a modest decline in retinol levels throughout pregnancy, which may be attributed to hemodilution, and depletion of maternal stores due to fetal demands. The fact that the majority of women were smokers could contribute to the inferior vitamin A status, as smoking seems to attenuate serum levels of beta-carotene [43].…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies [13, 42], we observed a modest decline in retinol levels throughout pregnancy, which may be attributed to hemodilution, and depletion of maternal stores due to fetal demands. The fact that the majority of women were smokers could contribute to the inferior vitamin A status, as smoking seems to attenuate serum levels of beta-carotene [43].…”
Section: Discussionsupporting
confidence: 92%
“…This supplement should contain the following at a minimum: copper (2 mg), zinc (15 mg), selenium (50 μg), folic acid (5 mg), iron (45‐60 mg or >18 mg after AGB), thiamine (>12 mg), vitamin E (15 mg), and beta‐carotene (vitamin A, 5000 IU) (level 4). The retinol form of vitamin A should be avoided during pregnancy due to teratogenicity risk (level 2+), and supplementation should be adjusted to maintain concentrations within normal limits (level 2−) …”
Section: Nutrition and Micronutrient Monitoringmentioning
confidence: 99%
“…Given the risk associated with potential deficiencies in the periconception period, the following indices should be checked at least every 3 months in women planning to become pregnant after BS: serum folate or red blood cell folate (level 2−), serum vitamin B12 or transcobalamin (level 2−), serum ferritin, iron studies (including transferrin saturation), full blood count (level 2−), and serum vitamin A levels (level 2−) . In addition, the following should be monitored every 6 months: prothrombin time, international normalized ratio (INR) (level 2+), serum 25‐hydroxyvitamin D with calcium, phosphate, magnesium, and parathyroid hormone (PTH) (level 4), serum protein and albumin (level 2−), renal function and liver function tests (level 4), serum vitamin E (level 4), serum zinc, copper, and selenium (level 4).…”
Section: Nutrition and Micronutrient Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies showed that post-bariatric, pregnant women are more susceptible to developing anemia due to the increased demand and inadequate intake [13,15,65]. For instance, twenty-four women were grouped under the four bariatric surgeries they underwent; 69% developed anemia and underwent malabsorptive bariatric surgery (e.g., RYGB and LSG with duodenojejunal bypass) compared to AGB and LSG [13].…”
Section: Anemiamentioning
confidence: 99%